ACRMiner: An Incremental Approach for Finding Dense and Sparse Rectangular Regions from a 2D Interval Dataset - Dwipen Laskar; Anjana Kakoti Mahanta (IAES Indonesian Section, 2023)
In many applications, transactions are associated with intervals related to time, temperature, humidity or other similar measures.Â The term